Role of 18F-FDG PET/CT in Assessment of Recurrence and Metastases in Female Breast Carcinoma Patients in Relation to Immunohistochemical Markers: Emphasis on HER2 Status, SUVmax Correlation, and Alignment with 2025/2026 EANM/SNMMI Guidelines (Bangladesh Journal of Nuclear Medicine, 2026)
Objective: The objective of this study was to observe the 18F-FDG positron emission computed tomography (PET-CT) findings in relation to immunohistochemical characteristics (IHCs) in breast carcinoma (BC) patients treated by surgery and referred to the National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Patients and methods: A total of 163 patients came for an 18F-FDG PET-CT scan at NINMAS for either to observe therapy response or for follow-up in between July 2023 and June 2024 and were included. This retrospective study was carried out to assess the metastases or recurrence in relation to IHCs of postoperative BC patients by 18F-FDG PET-CT scan. Results: Age ranged from 26 to 86 years with an average of 52.07 ± 11.8, and the most common age group was between 41 and 50 years (30.67%). Among 163 patients, 152 had infiltrating ductal cell carcinoma, and other categories were 11 patients. Metastases observed in 44 patients (26.99%). Most common site of metastases was in axillary lymph nodes (63.64%) followed by bone (43.18%), lung (36.36%) and liver (9.09%). CA 15-3 was higher (average: 137) in patients with metastases compared to patients without metastases (average: 13.7). Triple-negative patients were 49, 16 with metastases. Triple positive were 10 patients, three with metastases. HER-2 negative with metastases was 29 cases (65.90%), and HER-2 positive with metastases was 15 cases (34.09%) with different combinations of ER and PR characteristics. Local recurrence was found in three cases, and all were HER-2 negative. In the case of HER-2 negative patients, 53.85% developed metastases within two years, which was 38.88% in HER-2 positive patients. The SUVmax of the metastatic site was also higher in HER-2 negative (average SUVmax: 7.5) than in HER-2 positive cases (average SUVmax: 5.5). There is no significant difference in the pattern of metastases. No individual factor was found independently associated with sites of metastases. Conclusion: This study shows HER-2 negative with different combinations of ER and PR characteristics, and triple negative cases show more metastases and recurrence than HER-2 positive cases. There is no difference in the pattern of metastases in HER-2 positive and negative patients.Bangladesh J. Nuclear Med. 29(1): 28-35, 2026